Tanggung Jawab Perawat terkait Rahasia Rekam Medik Elektronik - Atmojo, Fajar Widhi (PSHPM Untag Semarang, 2025)
The confidentiality of medical records is crucial in healthcare services to protect patient privacy and maintain trust in medical professionals. The implementation of electronic medical records (EMR) is mandated by Minister of Health Regulation No. 24 of 2022 to modernize medical documentation systems. However, EMR poses challenges in safeguarding patient data from potential breaches and unauthorized access. The healthcare sector has high data breach rates, necessitating adaptive regulations and stronger protection systems. Health Law No. 17 of 2023 reinforces the obligation of medical and healthcare personnel to maintain the confidentiality of medical records. Nurses face ethical and legal dilemmas in balancing data protection with service obligations. A comprehensive strategy is required through strict regulations, strengthened digital security infrastructure, and education for healthcare professionals to ensure patient data protection in the digital era. This study uses a normative juridical approach with a qualitative descriptive method to analyze legal regulations regarding the function of EMR in terms of legal responsibility in Indonesia. Nurses play a vital role in maintaining EMR confidentiality, as regulated by Health Law No. 17 of 2024 and Minister of Health Regulation No. 24 of 2022. Compliance with regulations is essential to prevent violations and legal sanctions. Improving nurse training, strengthening data security policies, enforcing strict penalties, and fostering collaboration between nurses and healthcare institutions are crucial for ensuring optimal protection of patient medical records